Correction: Value sets and the problem of redundancy in value set repositories. - Sigfried Gold; Harold P Lehmann; Lisa M Schilling; Wayne G Lutters (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0312289.].